Research on a Large Diameter Magnetic Fluid Seal With Thin-Wall Parts - Guo, Yunqi; Li, Decai; Zang, Guobao; Qi, Zhiqiang; Zhang, Zhili (Frontiers in Materials, 2022)
Magnetic fluid seal is a new type of sealing method, which has been applied in many fields. For some fields, such as aviation and aerospace, high sealing performance, large shaft diameter and small design space are required, which brings difficulties to sealing design. Therefore, it is necessary to study large diameter magnetic fluid seal with thin-wall parts. In this paper, the effects of seal clearance and shaft deflection on the magnetic field distribution of magnetic fluid seal are analyzed by finite element method. At the same time, the force of seal shaft in the assembly process is also simulated. The influence of the amount of magnetic fluid on the pressure resistance is analyzed. The low-temperature starting torque and high-temperature pressure resistance of magnetic fluid seal are experimentally studied, and the optimal injection amount of magnetic fluid is obtained. The research content of this paper can be used as a reference for the design of large diameter magnetic fluid seal with thin-wall parts.